PENGARUH KUALITAS LAYANAN, KOMPETENSI TENAGA PENJUAL DAN CITRA PERUSAHAAN TERHADAP KEPUTUSAN MENGGUNAKAN KEMBALI JASA PADA PT. MANDALA MULTIFINANCE CABANG PALU - Azis, Muh. Dona (Katalogis, 2014)
The objective of this research are (1) know and analyze simultaneous effect of service quality,Â sales force competency, and firms image on repurchase decision Service at PT. Mandala Multifinance Palu Branch, (2) know and analyze partially effects of service quality, sales force competency, and firms image on repurchase decision Service at PT. Mandala Multifinance Palu Branch. There are 98 respondents in this study that have been determined as the sample. Analysis method used in this research is multiple linear regression. The results show that: (1) service quality, sales force competency, and firms image performs simultaneously effect on repurchase decision Service at PT. Mandala Multifinance Palu Branch, (2) servive quality performs positive but not significant effect on repurchase decision Service at PT. Mandala Multifinance Palu Branch, (3) sales force competency and firms image partially performs positive and significant effect on repurchase decision Service at PT. Mandala Multifinance Palu Branch